PENERAPAN METODE DEMONSTRASI BERBASIS TUGAS UNTUK MENINGKATKAN KREATIVITAS DAN PRESTASI BELAJAR (Studi pada Mata Pelajaran Kimia Kelas X di SMA Negeri 1 Kikim Timur) - Mariani Mariani (UNIB Press, 2020)
This study aims to describe the application of the task-based demonstration method and to describe the effectiveness of the application of the task-based demonstration method to increase creativity and learning achievement in the tenth grade Chemistry subject at SMA Negeri 1 Kikim Timur. The research method used is Classroom Action Research (CAR) and quasi-experimental. The subjects of this study were students of class X at SMA Negeri 1 Kikim Timur in the second semester of the 2019/2020 academic year. The data collection method in this study used a task-based demonstration method observation sheet, creativity observation sheet, and learning outcomes test. The results of the study indicate that the application of the task-based demonstration method can increase creativity, learning achievement and effectively improve student learning outcomes in class X Chemistry at SMA Negeri 1 Kikim Timur.PENERAPAN METODE DEMONSTRASI BERBASISTUGAS UNTUK MENINGKATKANKREATIVITAS DANPRESTASI BELAJAR(Studi pada Mata PelajaranKimia Kelas X di SMA Negeri 1 KikimTimur)